# Laplace transform of the zeroth-order Bessel function [duplicate]

Consider $J_0$ the zeroth order Bessel function. I'm trying to compute the Laplace transform

$$\mathcal{L}[J_0](s) = \int_0^\infty J_0(t) e^{-st}dt,$$

but until now I couldn't find a good way to do it. Substituting the series for $J_0$ doesn't seem to be a good idea. The other thing I thought of, was using the differential equation for $J_0$. That is, we know that

$$t^2J_0''(t)+tJ_0'(t)+t^2J_0(t)=0,$$

so that multiplying by $e^{-st}$ and integrating we have

$$\int_0^\infty t^2 J_0''(t)e^{-st}dt+\int_0^\infty tJ_0'(t)e^{-st}dt+\int_0^\infty t^2J_0(t)e^{-st}dt=0,$$

but I couldn't get very far with this. What I could indeed notice is that the last integral may be rewritten as

$$\int_0^\infty t^2 e^{-st}J_0(t)dt=\int_0^\infty \left(tJ_0(t)\right)\left(-\dfrac{d}{ds}\left(e^{-st}\right)\right)dt=-\dfrac{d}{ds}\left[s\int_0^\infty tJ_1(t)e^{-st}dt\right],$$

but this doesn't seem to help. On the other hand the other two integrals I had no idea to deal with them.

So, how can we compute this Laplace transform in a good way?

## marked as duplicate by Hans Engler, mickep, user147263, Claude Leibovici calculus StackExchange.ready(function() { if (StackExchange.options.isMobile) return; $('.dupe-hammer-message-hover:not(.hover-bound)').each(function() { var$hover = $(this).addClass('hover-bound'),$msg = $hover.siblings('.dupe-hammer-message');$hover.hover( function() { $hover.showInfoMessage('', { messageElement:$msg.clone().show(), transient: false, position: { my: 'bottom left', at: 'top center', offsetTop: -7 }, dismissable: false, relativeToBody: true }); }, function() { StackExchange.helpers.removeMessages(); } ); }); }); Oct 18 '15 at 6:47

Honestly I'd probably go the route of using $$J_\alpha(x) = \sum_{m=0}^\infty \frac{(-1)^m}{m!\Gamma(m+\alpha+1)}\left(\frac{x}{2}\right)^{2m+\alpha}$$ With $\alpha = 0$ this boils down to $$J_0(x) = \sum_{m=0}^\infty \frac{(-1)^m}{(m!)^2}\left(\frac{x}{2}\right)^{2m}$$ and as a Laplace Transform you'd find $$\int_0^\infty J_0(x)e^{-st}\text{d}t = \sum_{m=0}^\infty \frac{(-1)^m}{(m!)^22^{2m}}\int_0^\infty x^{2m}e^{-st} \text{d}t$$ The meat of the problem is computing the transform $$\int_0^\infty x^{2m}e^{-st} \text{d}t$$ but that transform is well known to be $\frac{(2m)!}{s^{2m+1}}$, so it all comes down to $$\sum_{m=0}^\infty \frac{(-1)^m}{(m!)^22^{2m}}\cdot \frac{(2m)!}{s^{2m+1}}$$
Edit With some pointers from Weaam, we have $$\sum_{m=0}^\infty \frac{(-1)^m}{(m!)^22^{2m}}\cdot \frac{(2m)!}{s^{2m}} = \frac{1}{\sqrt{1+\left(\frac{1}{s}\right)^2}}$$ via Taylor Series definition. So $$\mathcal{L}\left[J_0\right](s)=\frac{1}{s}\left(\sum_{m=0}^\infty \frac{(-1)^m}{(m!)^22^{2m}}\cdot \frac{(2m)!}{s^{2m}}\right) = \frac{1}{\sqrt{1+s^2}}$$